Talking about mathematics in two languages: Can parental views inform the development of digital games for young children? - Lange, Troels; Meaney, Tamsin (NOMAD Nordic Studies in Mathematics Education, 2018)
In this article, the results are presented from a survey of parents’ views about the digital games that their young multilingual children play. Previous research has indicated that parents struggled to describe how their children were learning from playing digital games. The results from this study indicate that parents could provide information about the digital games and the mathematical language they invoked. This information could be useful in developing playful, digital games that support multilingual children to talk about mathematics. The survey also provides insights into the follow-up qualitative research studies that are needed to support the development of new digital games.